Le “Pot Belge” : hommage amical à un pays modèle pour l’étude des facteurs d’intégration territoriale - Claude Grasland (Belgeo)
Belgium has been for the author a continuous matter of theoretical and quantitative research on political geography since a quarter of century. Due to the very particular geometry of Belgium’s territory (length of internal linguistic border, specific position of the Brussels-Capital Region), the country offers exceptional opportunities of exploration of the relations between economic factors (spatial interaction) and political factors (territorial interaction). An analysis of the dynamic of the settlement system on the long term (1846-2009) and of the migration on a half-century (1955-2009) reveals the strong resilience of the country against forces of political division. Brussels is apparently the key element in favor of the unity of the country.